Kajian Atas Perbandingan Penyusutan Aktiva Tetap Menurut Akuntansi (Komersial) Dan Menurut Ketentuan Peraturan Perundang-Undangan Perpajakan - Suparman . (Jurnal Akuntansi, 2014)
The Existence Of Different Concepts, Measurements, Methods, And The Recognition Of Income And Expenses Between Accounting And Taxation Lead To Differences Between Accounting Income To Taxable Income.